CIVET COFFEE AGRO TOURISM ATTRACTIONS AS A COMPETITIVE ADVANTAGE STRATEGY IN IMPROVING MARKETING PERFORMANCE IN BALI - Pande Ketut Ribek; Ni Putu Ayu Sintya Saraswati (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2018)
All companies have unique and different strategies with the aim of winning the competition. Tight competition also motivates the management of companies and business people in the field of agro-tourism especially coffee civet agrotourism to provide the best service to their customers. The superiority or strength of the civet coffee product business is able to produce creative products and innovations in the form of ideas and ideas in creating new products. In winning the competition, a company must always be creative and innovative so that it is able to meet the needs of consumers according to their tastes and changing times. Therefore we need a marketing strategy model that is in accordance with the conditions of the company with a SWOT analysis so that in the future it is expected that coffee civet agrotourism can be more developed and the company's objectives can be achieved both short and long term goals. In this study aims to determine the variables that are strengths, weaknesses, opportunities and threats faced by coffee civet tourism in marketing their products and how to compile and recommend an effective and efficient alternative marketing strategy for Civet Country Civet Coffee. This research was conducted at Agrowisata Negari Luwak Kopi Desa Singapadu, Bali. The sample in the study consisted of four people namely General Manager, head of production, Human Resources (HR) manager, Director of Sales and Marketing. Especially for external respondents, the consideration was that respondents understood the marketing strategy so that all respondents were considered competent. Respondents from 15 consumers consisting of 5 repeater guests who often buy coffee civet products so that they are more aware of the taste, process in making products and the quality of coffee products.10 New consumers are guests who are coffee lovers. Data analysis techniques were carried out by SWOT analysis, IFE and EFE Matrix